Perbandingan Aktivitas Antioksidan Ekstrak Etanol,Etil Asetat, dan n-Heksan Daun Kayu Manis Hutan (Cinnamomum iners) Dengan Metode ABTS dan DPPH - Hendri Faisal; Azzura Ligo; Rizka Hasmi Nasution (PPNI UNIMMAN, 2025)
. Indonesia possesses remarkable biodiversity, including numerous medicinal plant species traditionally employed as natural therapeutic agents. Among these, Cinnamomum iners is widely utilized and is known to contain diverse bioactive compounds with reported antimicrobial, anti-inflammatory, and free radical–scavenging activities. This research focuses onevaluate the antioxidant activity of ethanol, ethyl acetate, and n-hexane extracts of wild cinnamon leaves (Cinnamomum iners) using the ABTS and DPPH methods. Extraction was carried out using the maceration method. The antioxidant effectiveness was measured by analyzing the IC₅₀ values through free radical scavenging activity using the ABTS and DPPH methods with a UV-Vis spectrophotometer. The antioxidant activity of Cinnamomum iners leaves assessed using the ABTS method revealed that the ethanol extract exhibited very strong activity with an IC50 value of 7.56 ppm, followed by the ethyl acetate extract with moderate activity (IC50 103.59 ppm), and the n-hexane extract with weak activity (IC50 188.64 ppm). In contrast, the DPPH assay showed that the ethanol extract demonstrated moderate antioxidant activity with an IC50 value of 168.03 ppm, the ethyl acetate extract exhibited weak activity (IC50 400.5 ppm), and the n-hexane extract displayed no antioxidant activity (IC50 2373.2 ppm).